The Influence of Social Media Promotion Effectiveness, Price Perception, and Brand Image on Consumer Purchase Intention of Mie Gacoan (Study at Jalan Taman Siswa Branch, Yogyakarta) - Maria Febiola Jesika; Eko Prasojo (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of social media promotion effectiveness, price perception, and brand image on consumer purchase intention at Mie Gacoan, Jalan Taman Siswa Branch, Yogyakarta. A quantitative survey was conducted with 200 respondents selected through purposive sampling, and the data were analyzed using multiple linear regression. The findings show that all three variables positively and significantly influence purchase intention, with brand image having the strongest effect. These results highlight the importance of strengthening brand image, optimizing social media promotion, and maintaining competitive pricing to enhance consumer purchase intention. Keywords: Social Media Promotion; Price Perception; Brand Image; Purchase Intention; Mie Gacoan